Evaluation of Gasoline Samples from Several Erbil Petrol Stations - Karim A. Younis; Hawbash Kh. Mahmood; Karwan M. Rahman; Kasim S. Hadi; Ahmed, Sangar (Zanco Journal of Pure and Applied Sciences, 2023)
Gasoline is one of the main petroleum products used in transportation sectors in the Kurdistan region. The amount of gasoline provided from official refineries present in the region, which cover only a small portion of the total gasoline demand. The second source, which is the main one, is provided from outside of the region by private companies and includes three grades of gasoline (regular, premium, and super). The third source is blended gasoline, prepared locally in the region. Accordingly, to evaluate the available gasoline in the region, more than 100 samples of the three grades of gasoline were collected from different oil stations in Erbil City. Physical and chemical specifications were carried out, including sulfur content, octane number (RON and MON), density, vapour pressure, distillation curve, aromatic content, and olefin content using ASTM methods. The obtained results were compared with regional standards, Iraqi standards and worldwide standards. The results revealed that the majority of the gasoline samples had greater sulfur content, greater vapour pressure, low Initial Boiling Point (IBP), low distillation temperature at 10% and regular 50% and final boiling points (FBP). In addition, the majority of samples failed to meet all specifications in tests conducted following international, Kurdistan and Iraqi standards. The low quality of gasoline leads to an increase the environmental pollution, increase fire hazards of cars, and destroyed engine cars.